KINERJA PRODUKSI AGROINDUSTRI TAHU DI DESA GADINGREJO KABUPATEN PRINGSEWU - Saleh, Yuliana; Haryono, Dwi; Ashari Kurniawan, M. (Journal of Food System & Agribusiness, 2023)
This study aims to analyze the raw material procurement system, production performance and profits of tofu agroindustry in Gadingrejo Village, Pringsewu Regency. The method used in this research is a case study on tofu agroindustry in Gadingrejo Village. The location determination was carried out purposively with the consideration that this agroindustry is one of the agroindustries in the largest tofu production center in Gadingrejo District. The research was carried out in May – June 2021. The data analysis method used is a qualitative and quantitative descriptive analysis method. The results of this study indicate that the production performance of tofu agroindustry, seen from the aspects of labor productivity, capacity, quality, speed of delivery, and flexibility, can be said to be good. The six components in the raw material procurement activities from the reality indicators are in line with expectations. The total profit earned by the tofu agroindustry from all types of tofu production is IDR 37,026,332.47/month with an R/C of 1.38, which means that the tofu agro-industry can be said to be profitable and feasible to develop.